2019
DOI: 10.1371/journal.pone.0216552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heart rate variability and behavior of electrocardiographic parameters in dogs affected by chronic Monocytic Ehrlichiosis

Abstract: Canine Monocytic Ehrlichiosis (CME) is a systemic disease prevalent in the entire world caused by the obligate intracellular bacteria Ehrlichia canis . The occurrence of myocarditis with a high prevalence of arrhythmias in dogs affected by this disease in the cytopenic phase has already been proven. This study aims to evaluate the concentrations of CK MB, cTnI and NT-proBNP in dogs affected by Ehrlichia canis in the chronic phase since the intense stimulation of the immune system can lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, this index calculates HRV due to cycles shorter than 5 min (Task Force of the European Society of Cardiology, 1996; Shaffer & Ginsberg, 2017). Since it is normalized by the length of the raw recording, its value is less variable than, for example, SDNN; for a 3 h recording, Bogucki & Noszczyk-Nowak (2017 ) found the value to be 190.75?76.12 ms, while Pirintr et al (2017 ) observed 128.7?9.4 ms for a 14 h recording, and Gianfranchesco Gianfranchesco Filippi et al (2019 ) obtained 216.9?74.28 ms in a 24 hours-long recording. Bogucki & Noszczyk-Nowak (2017) also observed that clinically normal dogs exhibited lower SDNNidx values (190.75?76.12 ms) when compared to dogs presenting SSS (341.4?56.69 ms), but higher than those presenting CMVD (117.21?70.5 ms).…”
Section: Time Domain Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, this index calculates HRV due to cycles shorter than 5 min (Task Force of the European Society of Cardiology, 1996; Shaffer & Ginsberg, 2017). Since it is normalized by the length of the raw recording, its value is less variable than, for example, SDNN; for a 3 h recording, Bogucki & Noszczyk-Nowak (2017 ) found the value to be 190.75?76.12 ms, while Pirintr et al (2017 ) observed 128.7?9.4 ms for a 14 h recording, and Gianfranchesco Gianfranchesco Filippi et al (2019 ) obtained 216.9?74.28 ms in a 24 hours-long recording. Bogucki & Noszczyk-Nowak (2017) also observed that clinically normal dogs exhibited lower SDNNidx values (190.75?76.12 ms) when compared to dogs presenting SSS (341.4?56.69 ms), but higher than those presenting CMVD (117.21?70.5 ms).…”
Section: Time Domain Methodsmentioning
confidence: 99%
“…For instance, Alfonso et al (2020 ) and Baisan et al (2020 ) performed SDNN analysis in dogs using 5 min recordings, and found similar results. On the other hand, Bogucki & Noszczyk-Nowak (2017 ) used three-hour ECG recordings, while Pirintr et al (2017 ) recorded for 14 hours, Hezzell et al (2018 ) used 30 min, and Gianfranchesco Filippi et al (2019 ) performed Holter recordings of 24 h, and all these studies came across very different results. These differences may not only be ascribed to different time recordings, but also to other factors such as time of the day, animal stress during recordings, and animal size.…”
Section: Time Domain Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of this enzyme helps detect heart damage in the chronic phase of CME. [14][15][16] In this context, the proteins TRP19 and TRP36 were used as antigens for indirect ELISAs to detect anti-E. canis antibodies in naturally infected dogs from an endemic area of Brazil. Possible associations between different variables that represent biochemical alterations were evaluated by canonical correlation tests, which can highlight the most important data occurring when specific antigens are used.…”
mentioning
confidence: 99%